Lack of association of group specific component haplotypes with lung function in smokers. Issue 9 (28th August 2003) - Kasuga, I; Paré, P D; Ruan, J; Connett, J E; Anthonisen, N R; Sandford, A J
Abstract : Background: Airway inflammation may affect the decrease in lung function that occurs in response to cigarette smoke, and is an important pathological feature in chronic obstructive pulmonary disease (COPD). Group specific component (GC) can act as an inflammatory mediator and may therefore have important influences on the inflammatory reaction in the airway. Several reports have described associations between GC haplotypes and COPD but these remain controversial. In addition, most of these studies were based on a small number of subjects. Methods: We have studied the contribution of GC haplotypes to the level of lung function in a large cohort of smokers with high or low lung function (mean FEV1 % predicted 91.8 and 62.6, respectively). The frequency of the three major GC haplotypes (1S, 1F and 2) was investigated in 537 individuals with high lung function and 533 with low lung function. Results: No significant difference was found in the frequency of any GC haplotype between the high and low lung function groups. There was also no significant difference between the groups in genotype frequency of the two single nucleotide polymorphisms that underlie the haplotypes. Conclusion: The GC haplotype does not contribute to reduced lung function in this cohort of smokers.